Structure and binding interface of the cytosolic tails of αXβ2 integrin - Chua, Geok-Lin (2013)
Integrins are signal transducer proteins involved in a number of vital physiological processes including cell adhesion, proliferation and migration. Integrin molecules are hetero-dimers composed of two distinct subunits, α and β. In humans, 18 α and 8 β subunits are combined into 24 different integrin molecules. Each of the subunit comprises a large extracellular domain, a single pass transmembrane segment and a cytosolic tail (CT). The CTs of integrins are vital for bidirectional signal transduction and in maintaining the resting state of the receptors. A large number of intracellular proteins have been found to interact with the CTs of integrins linking integrins to the cytoskeleton. Methodology/Principal Findings: In this work, we have investigated structure and interactions of CTs of the leukocyte specific integrin αXβ2. We determined the atomic resolution structure of a myristoylated CT of αX in perdeuterated dodecylphosphocholine (DPC) by NMR spectroscopy. Our results reveal that the 35-residue long CT of αX adopts an α-helical conformation for residues F4-N17 at the N-terminal region. The remaining residues located at the C-terminal segment of αX delineate a long loop of irregular conformations. A segment of the loop maintains packing interactions with the helical structure by an extended non-polar surface of the αX CT. Interactions between αX and β2 CTs are demonstrated by 15N-1H HSQC NMR experiments. We find that residues constituting the polar face of the helical conformation of αX are involved in interactions with the N-terminal residues of β2 CT. A docked structure of the CT complex indicates that a network of polar and/or salt-bridge interactions may sustain the heteromeric interactions.